Robotic Telescopes, Student Research and Education Proceedings, Vol 1, No 1 2018
DOI: 10.32374/rtsre.2017.016
|View full text |Cite
|
Sign up to set email alerts
|

The NASA/IPAC Teacher Archive Research Program (NITARP)

Abstract: NITARP, the NASA/IPAC Teacher Archive Research Program, partners small groups of predominantly high school educators with research astronomers for a year-long research project. This paper presents a summary of how NITARP works and the lessons learned over the last 13 years. The program lasts a calendar year, January to January, and involves three week-long trips: to the American Astronomical Society (AAS) winter meeting, to Caltech in the summer (with students), and back to a winter AAS meeting (with students)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this section, the NITARP project is very briefly described. For a longer description of the program, please see Rebull et al [20,21]. Because the present paper includes a discussion on the longer-term impacts of NI-TARP on its participants, this section also highlights the ongoing community of NITARP alumni.…”
Section: Nitarp Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, the NITARP project is very briefly described. For a longer description of the program, please see Rebull et al [20,21]. Because the present paper includes a discussion on the longer-term impacts of NI-TARP on its participants, this section also highlights the ongoing community of NITARP alumni.…”
Section: Nitarp Overviewmentioning
confidence: 99%
“…Other recent papers describe NITARP in more detail [21]; see Rebull et al [20] for more discussion specifically about the motivations of educators for participating in NITARP, with ramifications for supporting teachers through a research program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some approaches to dealing with instructors confidence is to provide authentic research experiences (e.g. [166,167]) to increase their understandings of the nature of science. Prior experience with research has been shown to have the strongest correlation to accurate knowledge of the nature of science and scientific inquiry on behalf of the instructor [168].…”
Section: Instructor Barriersmentioning
confidence: 99%
“…Research Experiences for Teachers (Silverstein et al, 2009), the NASA-IPAC Teacher Archive Research Project (Rebull et al, 2015), and Pulsar Search Collaboratory (Rosen et al, 2013) are all examples of such programs. As discussed in Chapter 1, such experiences can significantly benefit young learners.…”
Section: Implications For Policy and Practicementioning
confidence: 99%